SURVEI TINGKAT PENGETAHUAN TENTANG KEAMANAN PENGGUNAAN OBAT PADA IBU MENYUSUI DI PUSKESMAS SUMBERSARI KABUPATEN JEMBER - Norcahyanti, Ika (Brawijaya University, 2018)
On lactation a mother can experience a variety of health complaints or disorders that require the use of the medicine, so many mothers who are breastfeeding using drugs that can give undesirable effects on the baby's feedings. Some drugs with certain characteristics can be mixed into the breast milk. The characteristics referred to, among others, is a drug that is easily soluble in fats, a drug that has the weight of small molecules, ionized drugs, and drugs that bind weakly with plasma proteins. The level of knowledge of nursing mothers will drug safety is a crucial factor to safeguard the safety of the baby. When nursing mothers have a good level of knowledge will be drug safety throughout lactation, so baby can escape from the dangers of drug side effects. This research is a survey research with cross-sectional design against 100 people respondents in Sumbersari Clinics at Jember Regency. The sample of respondents is selected using a purposive sampling technique. Before the questionnaires distributed to respondents, first conducted the test validity and reliability tests. Category level of knowledge of nursing mothers about the safety of the drugs are divided into 3 categories, namely low, medium, and high. Reference to that category, taken from the average rating ± SD knowledge of nursing mothers. Descriptive analysis shows average values ± SD i.e of 6.5 ± 2.4, so for a value of between 4.1-8.9 are included in the category of being. Values smaller than 4.1 fall into the low category and values greater than 8.9 fall into the high category. The results showed that breastfeeding mothers who have low knowledge level of 20%, the level of knowledge being of 57% and a high level of knowledge of 23%. Research results also showed that based on the security level of drug use in accordance with the WHO is a year of 2003, drugs consumed by nursing mothers is made up of the drug with a security level of category one (amoxicillin, mefenamic acid, dextromethorphan HBr, ibuprofen, paracetamol, and tetracycline), drugs with a security level of category two (acetylsalicylic acid and ephedrine HCl), as well as a drug with a security level of category three (chlorphenamine).